Comparison of Oral Health Indices and Xerostomia in Students Using Traditional and Electronic Cigarettes at Mazandaran University of Medical Sciences, 2024 - Maedeh Salehi; Melika Mollaei; Negar Mohammadi; Hodis Ehsani; Mohammadjavad Abdoli; Abolfazl Hosseinnataj; Tahereh Mollania (Journal of Mazandaran University of Medical Sciences, 2025)
Background and purpose: Smoking is a major risk factor for poor oral health. This study aimed to compare periodontal indices, salivary pH, xerostomia, and the Decayed, Missing, and Filled Teeth (DMFT) index among students using traditional cigarettes and electronic cigarettes at Mazandaran University of Medical Sciences in 2024. Materials and methods: In this cross-sectional study, a total of 105 students were included and categorized into three groups: traditional cigarette smokers, electronic cigarette users, and non-smokers. Demographic data were obtained from student records, and clinical oral examinations were conducted to assess the gingival index (GI), plaque index (PI), bleeding on probing (BOP), and the DMFT index. Xerostomia was evaluated using a 9-item questionnaire, and salivary pH was measured using pH indicator strips. Data were analyzed using SPSS version 22, with a significance level set at P< 0.05. Results: The findings indicated a significant difference between the three groups in terms of gender distribution and average duration of smoking (P < 0.05). The GI and PI were significantly higher in the traditional cigarette group compared to both the non-smoker and electronic cigarette groups (P < 0.05). Conversely, the BOP index was significantly lower in the traditional cigarette group than in the non-smoker group (P = 0.009). The DMFT index was significantly lower in the non-smoker group compared to both the traditional cigarette (P = 0.005) and electronic cigarette (P = 0.008) groups. Among all participants, 4.8% reported experiencing dry mouth, with no statistically significant difference observed between the three groups. Conclusion: This study highlights the harmful effects of traditional cigarette use and suggests that electronic cigarettes may be a less harmful alternative. However, both traditional and electronic cigarette use were associated with increased salivary acidity, indicating potential adverse effects on oral health.